L’exploitation méconnue d’une ressource connue: la collecte des larves comestibles de charançons dans les palmiers raphias au sud Cameroun - Dounias, E. (Peeters-SELAF, 2003)
As far as entomophagy is concerned, the first resource that comes to mind concerning the Congo Basin area is the improperly called ‘white worm of palm trees’. This weevil larva (Rhynchophorus phoenicis F., Curculionidae) is commonly known, and if we except local and specific food prohibitions, it is widely appreciated as food throughout Central Africa. This resource is frequently mentioned in the literature dealing with food consumption in this region, with precise information about its nutritional value. Nevertheless, there exists no detailed description of gathering processes. Data are elusive concerning the economic value of this NTFP, which is usually perceived as a ‘delicacy’ rather than as a resource of considerable value.